2019
DOI: 10.1021/acs.jpcc.9b02286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bias Voltage on a Single-Molecule Junction Investigated by Surface-Enhanced Raman Scattering

Abstract: We have investigated the effect of the bias voltage on the 1,4-benzenethiol (BDT) single-molecule junction using the surface-enhanced Raman scattering (SERS). By measuring the bias voltage dependence of SERS for the identical sample, we can clearly observe the blue shift of the vibrational mode at 355 cm–1 by the application of the bias voltage. This measurement is possible by using a highly stable nanogap electrode which is fabricated with lithographic techniques. Meanwhile, the energy of other vibrational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…22,23 This combination of measurements of the electric properties gives precise information about the structure 21,24 and insights into the fundamental physics underlying the vibration-related energy transport. 16,17 Although these combination measurements have revealed the structures of SMJs, further investigations are expected to elucidate the interaction between the metal and molecule by clarifying the effect of the contact geometry.…”
mentioning
confidence: 99%
“…22,23 This combination of measurements of the electric properties gives precise information about the structure 21,24 and insights into the fundamental physics underlying the vibration-related energy transport. 16,17 Although these combination measurements have revealed the structures of SMJs, further investigations are expected to elucidate the interaction between the metal and molecule by clarifying the effect of the contact geometry.…”
mentioning
confidence: 99%
“…investigated the influence of bias voltage on SERS for the BDT single‐molecule junction (Figure 11f). [ 69 ] The vibrational mode at 355 cm –1 , which was corresponded to the out‐of‐plane mode of the aromatic ring, showed blue shift when a bias voltage was applied (Figure 11g). [ 69 ] The theoretical calculations demonstrated that the bias voltage effects on SERS originated from the rearrangement of the π system, which was delocalized on thiol S in the primitive BDT single‐molecule junction.…”
Section: Application Of On‐chip Molecular Junction In Sersmentioning
confidence: 99%
“…[ 69 ] The vibrational mode at 355 cm –1 , which was corresponded to the out‐of‐plane mode of the aromatic ring, showed blue shift when a bias voltage was applied (Figure 11g). [ 69 ] The theoretical calculations demonstrated that the bias voltage effects on SERS originated from the rearrangement of the π system, which was delocalized on thiol S in the primitive BDT single‐molecule junction. This delocalization was suppressed when a bias voltage applied, resulting in the out‐of‐plane mode of the aromatic ring shifted to higher energy.…”
Section: Application Of On‐chip Molecular Junction In Sersmentioning
confidence: 99%
“…Vibrational transport in single OPE-3 molecules has been investigated theoretically and measured electrically in the coherent tunneling regime. 8,33−36 These studies show that electron transport through the molecular junction 37,38 can result in additional vibrational resonances. 39,40 We measure the near-field enhanced Raman spectrum from 500 to 2500 cm −1 to characterize the vibrational spectrum of the molecular junction and suggest that we can control the vibrational resonances using the local angular momentum induced by incident laser beams on the tip of the tunneling microscope.…”
mentioning
confidence: 99%
“…A molecular “wire” of fully π-conjugated oligo­(phenylene ethynylene)-3 ( OPE-3 ) electrically connects the metal-coated tip of a tunneling microscope to a metal substrate (Figure ). Vibrational transport in single OPE-3 molecules has been investigated theoretically and measured electrically in the coherent tunneling regime. , These studies show that electron transport through the molecular junction , can result in additional vibrational resonances. , We measure the near-field enhanced Raman spectrum from 500 to 2500 cm –1 to characterize the vibrational spectrum of the molecular junction and suggest that we can control the vibrational resonances using the local angular momentum induced by incident laser beams on the tip of the tunneling microscope. Using the incident lasers as inputs and the Raman spectrum as an output, we demonstrate five logic operations (gates), specifically, AND, OR, XNOR, TRUE, and NOT A.…”
mentioning
confidence: 99%